PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN MINAT DAN PEMAHAMAN MATERI ZAKAT PADA SISWA SMP KELAS IX SMP NEGERI 1 WONODADI BLITAR - Titin Erviana Ayu Neni; Thias Arisiana; Rohmah Ivantri; Arif Susanto; Abidatul Kholisoh (LPPM STAI Muhammadiyah Probolinggo, 2026)
The low level of students’ interest and understanding of zakat material is one of the challenges in Islamic Religious Education at the junior high school level. Zakat material is often perceived as difficult and tedious due to conventional teaching approaches and limited student interaction. This study aims to improve the interest and comprehension of Grade IX students in zakat material through the implementation of the Jigsaw cooperative learning model. This research was conducted as Classroom Action Research (CAR) in two cycles, each consisting of planning, action, observation, and reflection phases. The research subjects were 27 ninth-grade students. Data were collected through observation, learning interest questionnaires, and comprehension tests. In the pre-cycle, the students' average score was 63.63 with a mastery level of 33%. After implementing the Jigsaw model, the results in Cycle I showed an increase in the average score to 69.81 with 41% mastery, and in Cycle II it significantly increased to 78.70 with 100% mastery. Additionally, students showed increased participation, active engagement in group discussions, and enthusiasm toward learning zakat. The Jigsaw model encouraged students to take more responsibility in understanding the material since they were required to explain their assigned part to their peers. The study concludes that the Jigsaw cooperative learning model is effective in enhancing students’ interest and understanding of zakat material through an active, collaborative, and meaningful learning process.